Bagaimana Konsumen Kosmetik Memerhatikan Beauty Vlogger dan Pengaruhnya terhadap Niat Beli - Lika Alda Septiani (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study aims to determine the effect of physical attractiveness, attitude homophily, social attractiveness, credibility, and parasocial interaction on cosmetics purchase intention based on the TasyaFarasya review. TasyaFarasya is one of the beauty vloggers on YouTube and Instagram. This study uses a quantitative approach. The sampling technique used is non-probability sampling which is judgmental sampling. In this study, the respondents are women; they knew TasyaFarasya as a beauty vlogger; the age is around 17-35 years and watched content from TasyaFarasya. The number of samples is 200 respondents. The data was processed using PLS-SEM with SmartPLS software version 3.3.3. The findings of this study indicate that physical attractiveness, homophily attitudes have a significant effect on credibility. While physical attractiveness and social attractiveness significantly affect parasocial interactions, homophily attitudes do not affect parasocial interactions. Credibility does not affect purchase intention, but parasocial interaction has a significant effect on purchase intention. Further research can add information and building motive variables. It is also interesting to see further how the interaction between vlogger viewers.